Neolithic Artifacts: source and mobility in Alentejo (Portugal) - Sissay, Fikeru Mekonenn (2022)
A set of 15 late prehistoric polished stone tools from the Perdigões ditched enclosure (Reguengos de Monsaraz, south Portugal), occupied during the Neolithic-Chalcolithic (late 4 th to 3rd millennium BC), was studied with the objective of establishing geological provenance and also to evaluate the application of a nondestructive methodology for provenance studies. Complementary techniques, namely optical petrographic analysis, powder X-ray diffraction (pXRD), in-situ X-ray diffraction (in-situ XRD), X-ray fluorescence spectroscopy (XRF and p-XRF) and scanning electron microscope coupled with energy dispersive spectroscopy (SEM-EDS), were implemented to perform the analysis. The 15 samples of polished stone revealed a predominance of metamorphic raw materials such as amphibolite or greenschist mineral phases but also two igneous rocks such as an andesite and a diorite. The petrographic and geochemical diversity of the artifacts does not show a clear match with the various potential outcrops studied. The results obtained suggest a non local or non-peripheral (10–60 km from Perdigões) source of raw material for the production of polished stone artifacts. As a result, this study may confirm the existence of objects exchanged through favorable networks and communication, demonstrating the trajectories that Southwest Iberian societies took as they engaged in increased social complexity. The combination of conventional petrographic and geochemical analysis proved to be the best approach for provenance studies. The application of a nondestructive methodology in the study of these materials revealed some limitations: the in-situ XRD did not show the chlorite and mica (visible in powder) that can be crucial to relate to geological contexts, and the p-XRF allowed the establishment of geochemical clusters but with a battery of a limited set of elements capable of differentiating these lithological varieties. Nevertheless, the combination of petrographic and multielemental analyses by combining SEM-EDS with p XRF and in-situ XRD could provide a viable way of determining the provenance of polished stone tools, and the results can contribute to a better understanding of past societies RESUMO: Artefatos Neolíticos: Origem e Mobilidade no Alentejo (Portugal) Um conjunto de 15 ferramentas de pedra polida provenientes do Complexo arqueológico dos Perdigões (Reguengos de Monsaraz, Sul de Portugal), ocupado durante o Neolítico-Calcolítico (finais do 4.º a 3.º milénios a.C.), foi estudado com o objetivo de estabelecer a proveniência geológica e também avaliar a aplicação de uma metodologia não destrutiva em estudos de proveniência. Técnicas complementares, nomeadamente análise petrográfica óptica, difracção de raios X em pó (pXRD), difração de raios X in situ (in situ XRD), espectroscopia de fluorescência de raios X (XRF e p-XRF), e microscópio eletrónico de varrimento acoplado a energia dispersiva espectroscopia (SEM-EDS) foram implementadas para realizar as análises. As 15 amostras de pedra polida revelaram uma predominância de matérias-primas metamórficas como anfibolito ou fases minerais típicas dos xistos verdes, mas também duas rochas ígneas como um andesito e um diorito. A diversidade petrográfica e geoquímica encontrada nos vários artefactos não encontra um paralelo claro e inequívoco com os vários afloramentos potenciais estudados. Os resultados obtidos sugerem uma fonte não local ou não periférica (10-60 km de Perdigões) de matéria-prima para a produção de artefactos de pedra polida. Como resultado, este estudo confirma a existência de troca de objetos por meio de redes e comunicação favoráveis, demonstrando as trajetórias nas quais as sociedades do Sudoeste Ibérico se prestaram no aumento da complexidade social. A combinação de análise petrográfica e geoquímica convencionais mostrou ser a melhor abordagem para estudos de proveniência. A aplicação de uma metodologia não destrutiva apenas no estudo destes materiais revelou algumas dificuldades; a XRD in situ que não apresenta a clorite e a mica (visível em pó) que podem ser cruciais para relacionar com contextos geológicos e a p-XRF que permite o estabelecimento de clusters geoquímicos, mas com uma bateria de conjunto limitado de elementos capazes de diferenciar estas variedades litológicas. No entanto, a combinação de análise petrográfica e multielementar combinando SEM-EDS com p-XRF e in-situ XRD pode fornecer uma primeira aproximação viável na determinação da proveniência de ferramentas de pedra polida, e os resultados podem contribuir para uma melhor compreensão das sociedades passadas.